A Systematic Review On The Outcomes Of Fibular Strut Graft For Femoral Neck Fractures In Adults - Bintang Soetjahjo; Udi Heru Nefihancoro; Rieva Ermawan; Gilang Teguh Pratama (Biomolecular and Health Science Journal, 2021)
Introduction: Femoral neck fractures are a type of intracapsular hip fracture which also be found in younger patients who suffered from high-energy trauma such as vehicle accidents. Non-union and avascular necrosis are the most frequent complications following femoral neck fractures. In this study, we reviewed the outcomes of fibular grafting techniques for femoral neck fractures in adults.Methods: Online libraries PubMed, Cochrane Library and Scopus were searched for relevant papers. We searched for scientific publications published between 2009 and 2020. Inclusion and exclusion criteria were used, and prespecified characteristic were extracted from each study.Results: We found 172 papers relevant to the topic. At last, we included 6 papers in this systematic review with a total of 198 patients. Fibular strut graft for femoral neck fractures have shown excellent outcomes, uniting 177 (89,39%) of 198 fractures reviewed. Overall, 15 patients (7,57%) experiencing non-union and 12 patients (6,06%) having avascular necrosis.Conclusion: The outcomes of the intervention turned out to be excellent, assessed by both functional outcome criteria and radiographic bony union. It is important to established a consensus on surgical intervention for femoral neck fractures, specifically including fibular strut grafting.